Legal Protection for Nasional Health Insurance (JKN) Participants in the Case of Default in Health Facility Services Based on Health Law Number 17 of 2023 - Samira Samira; Irsyam Risdawati; Redyanto Sidi (Journal Evidence Of Law, 2026)
This study aims to examine legal protection for National Health Insurance (JKN) participants in dealing with cases of default in health facility services, with reference to Health Law Number 17 of 2023. The main focus of the research is to understand the extent to which this law provides legal protection for the rights of JKN participants, especially when the health services received are not in accordance with the applicable provisions. Through a normative approach, this study analyzes the provisions contained in the law related to the obligations of health facilities and the rights of JKN participants, as well as the legal impact in the event of a default in health services. This study also identifies forms of default that may occur in the context of implementing JKN, both from the health facility and the JKN program organizer itself. By using an analytical legal approach, it is hoped that solutions can be found to improve the protection mechanism for participants, including legal remedies that can be taken by JKN participants if their rights are not fulfilled. In this study, it is also discussed about the role of supervision and sanctions given to parties who commit defaults, as well as the government's obligation to ensure that health services provided to JKN participants are in accordance with the set standards. Through the results of the analysis, this study concluded that although Health Law Number 17 of 2023 provides a strong legal basis to protect the rights of JKN participants, there are still gaps in its implementation that can harm participants. Therefore, it is recommended that there be increased supervision, a better understanding of the rights of JKN participants, and stricter law enforcement against health facilities that commit defaults. This research makes an important contribution to the development of the health legal system in Indonesia.